The impact of repeated temperature cycling on cryopreserved human iPSC viability stems from cytochrome redox state changes - Okuda, Jun; Watanabe, Namiko; Nakamura, Tetsuji; Mizushima, Kenta; Xi, Heqi; Kumamoto, Yasuaki; Fujita, Katsumasa; Kino-Oka, Masahiro (Frontiers in Bioengineering and Biotechnology, 2024)
Human induced pluripotent stem cells (hiPSCs) are an attractive cell source for regenerative medicine. For its widespread use as a starting material, a robust storage and distribution system in the frozen state is necessary. For this system, managing transient warming during storage and transport is essential, but how transient warming affects cells and the mechanisms involved are not yet fully understood. This study examined the influence of temperature cyclings (from -80 °C to -150 °C) on cryopreserved hiPSCs using a custom-made cryo Raman microscope, flow cytometry, and performance indices to assess viability. Raman spectroscopy indicated the disappearance of mitochondrial cytochrome signals after thawing. A reduction in the mitochondrial membrane potential was detected using flow cytometry. The performance indices indicated a decrease in attachment efficiency with an increase in the number of temperature cycles. This decrease was observed in the temperature cycle range above the glass transition temperature of the cryoprotectant. Raman observations captured an increase in the signal intensity of intracellular dimethyl sulfoxide (DMSO) during temperature cycles. Based on these results, we proposed a schematic illustration for cellular responses to temperature fluctuations, suggesting that temperature fluctuations above the glass-transition temperature trigger the movement of DMSO, leading to cytochrome c oxidation, mitochondrial damage, and caspase-mediated cell death. This enhances our understanding of the key events during cryopreservation and informs the development of quality control strategies for hiPSC storage and transport.